Review—Carbon Cloth as a Versatile Electrode: Manufacture, Properties, Reaction Environment, and Applications. Issue 5 (1st May 2022) - León, María I.; Castañeda, Locksley F.; Márquez, Ana A.; Walsh, Frank C.; Nava, José L.
Abstract : The manufacture, characterisation and application of carbon cloth (CC) are reviewed and its use as an electrode in fundamental electrochemical studies and technological applications over the last fifty-five years is considered. The most widely used precursors to produce commercial CC are polyacrylonitrile (PAN) fibres manufactured by heat treatment at 1500–2000 o C. Carbon cloth has good electrical conductivity, high mechanical strength and high chemical resistance. CC is a versatile electrode material that can operate over a wide potential range in aqueous electrolytes and molten salts. Chemical and thermal methods can enhance the surface area and help control CC surfaces' wettability. Electrodes can be decorated by nanostructured carbons, precious metal nanoparticles or enzyme immobilisation to modify surface functionality, improve activity and widen applications. The doping of CC with polymers, metals and metal oxides has enabled its use in sensors, electrosynthesis of chemicals, environmental remediation and water treatment, as well as energy storage and conversion. Electrochemical cells incorporating CC ranging from three-electrode laboratory bench cells to pilot plant flow cells are illustrated. The characterisation of hydrodynamics, mass transport rates and potential/current distributions in CC-equipped flow cells using experimental and computational fluid dynamics approaches are analysed. Finally, continuing research challenges to CC are highlighted.